Dexmedetomidine for Awake Intubation Procedure in Subtotal Thyroidectomy - Riyanti, Riandini Pramudita; Hapsari, Paramita Putri (Journal of Anaesthesia and Pain, 2022)
Background: Giant struma makes airway management difficult for the anesthesiologist due to the risk of tracheal intubation failure. Awake fiberoptic intubation(AFOI) is the gold standard in the management of a predicted difficult airway. Giving analgesia and sedation can facilitate operator and patient comfort during the awake intubation procedure.Case: We report the case of a 63-year-old woman with a giant struma who was planned for a subtotal thyroidectomy. We provide ondansetron and dexamethasone premedication, analgesia and sedation using dexmedetomidine, propofol induction, muscle relaxant atracurium, with maintenance anesthetic sevoflurane. Dexmedetomidine was administered on loading dose 0.8 Âµg /kg/hour in the first 10 minutes then continue on analgesia dose 0.2 Âµg /kg. During the AFOI procedure, 100% oxygenation was given with the patient's hemodynamic range, namely systolic blood pressure of 110-131 mmHg, diastolic blood pressure of 75-93 mmHg, heart rate of 77-91 beats per minute, and SpO2 of 98-100%. Postoperatively the patient was transferred to the Intensive care unit (ICU) with an endotracheal tube intube. Monitoring of postoperative complications such as production of thyroid crisis drainage and extubation 24 hours after surgery was confirmed by the cuff leak test.Conclusion: Giving dexmedetomidine is better than opioids in the AFOI procedure because of its minimal respiratory depressant effect. Maintaining hemodynamic stability during the AFOI procedure is very important to avoid hemodynamic fluctuations so it can minimize the risk of perioperative complications.